Photodynamic therapy combined with surgery versus Mohs micrographic surgery for the treatment of difficult-to-treat basal cell carcinoma: a retrospective clinical study - Nianzhou Yu; Lisha Wu; Juan Su; Mingliang Chen; Lixia Lu; Kai Huang; Yixin Li; Zixi Jiang; Siliang Liu; Lanyuan Peng; Yang Xie; Zeyu Chen; et al. (Taylor & Francis Group, 2023)
Background Mohs micrographic surgery (MMS) is the preferable surgery for difficult -to-treat basal cell carcinoma (BCC) but is an expensive, labor-intensive, and time-consuming technique. The aim of this study is to compare the efficacy and safety of photodynamic therapy combined with surgery(S-PDT) versus Mohs micrographic surgery (MMS) for the treatment of difficult-to-treat BCC. Methods This was a retrospective, comparative study. A total of 32 patients, 16 patients with 48 lesions, were treated with S-PDT, and the other 16 patients with 17 lesions treated by MMS were enrolled in this study. Follow-up was at least 36 months posttreatment. Results The recurrence rate was no statistical difference between the S-PDT and MMS (p = 1.000, Fishers exact test). The median follow-up was 42.5 months (range 36-63 months). The mean healing time in the S-PDT [17.9 d (SD 9.8)] is longer than in MMS [7.5 d (SD 1.5)] during follow-up (p＜.001, Independent T-test). On the whole, the cosmetic outcome of patients in S-PDT was statistically no significant difference with that in MMS according to a 4-point scale (p = .719, chi-squared test). Conclusions S-PDT is a safe, effective, and novel cosmetic treatment, which holds the potential to be an alternative treatment to MMS for some cases.